Lower temperatures reduce type I interferon activity and promote alphaviral arthritis - Natalie A. Prow; Bing Tang; Joy Gardner; Thuy T. Le; Adam Taylor; Yee Suan Poo; Eri Nakayama; Thiago Dominguez Crespo Hirata; Helder I. Nakaya; Andrii Slonchak; Pamela Mukhopadhyay; Suresh Mahalingam; et al. (2017)
Chikungunya virus (CHIKV) belongs to a group of mosquito-borne alphaviruses associated with acute and chronic arthropathy, with peripheral and limb joints most commonly affected. Using a mouse model of CHIKV infection and arthritic disease, we show that CHIKV replication and the ensuing foot arthropathy were dramatically reduced when mice were housed at 30°C, rather than the conventional 22°C. The effect was not associated with a detectable fever, but was dependent on type I interferon responses. Bioinformatics analyses of RNA-Seq data after injection of poly(I:C)/jetPEI suggested the unfolded protein response and certain type I interferon responses are promoted when feet are slightly warmer. The ambient temperature thus appears able profoundly to effect anti-viral activity in the periphery, with clear consequences for alphaviral replication and the ensuing arthropathy. These observations may provide an explanation for why alphaviral arthropathies are largely restricted to joints of the limbs and the extremities.